Ureteric lesions detected in normally functioning kidney allografts: risk factors and clinical implications - Figueiredo, AJ (2005)
INTRODUCTION: We characterized the alterations in ureteral biopsies from normally functioning kidney allografts to study risk factors. MATERIALS AND METHODS: We studied 55 ureteral fragments from kidney grafts obtained during cystoscopy for routine double-J stent extraction. We evaluated the type and severity of the lesions, the risk factors for their occurrence, and their relation to the evolution of the transplant, including the occurrence of renal rejection episodes or ureteral complications. RESULTS: Borderline or rejection lesions were detected in 21 of the 55 fragments. Rejection lesions were more common among biopsies performed in the first 80 days (54.6%) than during the 120 days afterward (15.4%, P = .043). Similarly, urothelium reactivity was detected in 71.4% and 30.7% of the biopsies performed up to and after 4 months, respectively (P = .008). Urothelial atrophy was detected in 20% of the fragments, the age of the donors being higher in these cases (P = .026). There was a trend to the association of borderline or rejection lesions in the ureteral biopsies and a history of an acute renal rejection episode (P = .053). There were no detectable relations between those findings and the evolution of the transplant. CONCLUSIONS: Thirty-eight percent of the biopsed ureters showed rejection or borderline lesions, these lesions were more common among biopsies done in the first months after transplantation. These findings are similar to the ones found in routine renal biopsies. We did not find any significant relation between the nature of the lesions encountered on the ureteral biopsies and the evolution of the transplant.